Development of Novel Fluorinated Polyphenols as Selective Inhibitors of DYRK1A/B Kinase for Treatment of Neuroinflammatory Diseases including Parkinson's Disease - Gian Luca Araldi; Yu-Wen Hwang (MDPI AG, 2023)
Natural polyphenol derivatives such as those found in green tea have been known for a long time for their useful therapeutic activity. Starting from EGCG, we have discovered a new fluorinated polyphenol derivative (1c) characterized by improved inhibitory activity against DYRK1A/B enzymes and by considerably improved bioavailability and selectivity. DYRK1A is an enzyme that has been implicated as an important drug target in various therapeutic areas, including neurological disorders (Down syndrome and Alzheimer's disease), oncology, and type 2 diabetes (pancreatic β-cell expansion). Systematic structure-activity relationship (SAR) on trans-GCG led to the discovery that the introduction of a fluoro atom in the D ring and methylation of the hydroxy group from para to the fluoro atom provide a molecule (1c) with more desirable drug-like properties. Owing to its good ADMET properties, compound 1c showed excellent activity in two in vivo models, namely the lipopolysaccharide (LPS)-induced inflammation model and the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) animal model for Parkinson's disease.